Impacts of invasive birds: assessing the incidence and extent of hybridization between invasive Mallard Ducks (Anas platyrhynchos) and native Yellow-billed Ducks (Anas undulata) in South Africa - Stephens, Kirstin (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.